2020
DOI: 10.1002/andp.201900601
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Integrability of 1D Ionic Hubbard Model

Abstract: The quantum integrability of the 1D ionic Hubbard model (IHM) is established using two independent numerical methods, namely i) energy level spacing statistics and ii) occupation profile of one‐particle density matrix (OPDM) eigen‐values. Both methods suggest that the 1D IHM is integrable. The calculations of energy level statistics reproduce the known results for the standard Hubbard model. Upon turning on the the ionic term, the energy level spacing distribution of this model continues to obey the Poissonian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…Similar reports using compounds with suggested antioxidant properties such as resveratrol [134], Licochalcone A [135], diallyl disulfide [136], Pterostilbene [137], wogonin [138], prontandin, and 6-gingerol [139] have all been shown to exert anti-inflammatory and chondroprotective properties in joint tissues through activation of Nrf2 pathways. These lines of evidence demonstrate the importance of the Nrf2 signaling pathways in maintaining redox balance and chondrocyte homeostasis during aging and in OA but the precise signaling pathways that elicit these effects remain incompletely understood.…”
Section: Nuclear Factor-erythroid 2-related Factor (Nrf2) In Aging and Cartilagesupporting
confidence: 63%
“…Similar reports using compounds with suggested antioxidant properties such as resveratrol [134], Licochalcone A [135], diallyl disulfide [136], Pterostilbene [137], wogonin [138], prontandin, and 6-gingerol [139] have all been shown to exert anti-inflammatory and chondroprotective properties in joint tissues through activation of Nrf2 pathways. These lines of evidence demonstrate the importance of the Nrf2 signaling pathways in maintaining redox balance and chondrocyte homeostasis during aging and in OA but the precise signaling pathways that elicit these effects remain incompletely understood.…”
Section: Nuclear Factor-erythroid 2-related Factor (Nrf2) In Aging and Cartilagesupporting
confidence: 63%
“…In this appendix, we show how neglecting the separation into the different symmetry sectors the in principle GOE like distribution of the level spacings approaches the Poisson-like distribution. In particular, we focus on half filling, for parameters close to the ones considered in Hosseinzadeh et al [21] where the Poisson statistics was identified.…”
Section: Discussionmentioning
confidence: 99%
“…The level statistics of different many-body quantum systems have been classified as for example of the prime examples of the Hubbard model [20] and variants of it [21], or its bosonic counterpart [22], a kicked-parameter model of spinless fermions [23], or more recently a family of Sachdev-Ye-Kitaev models [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A lot of different many body quantum systems have been investigated. To mention just a few, the prime examples are the Hubbard model [26] and variants of it [27,28], or the Bose-Hubbard model [29], a kicked-parameter model of spinless fermions [30], or generalized Sachdev-Ye-Kitaev models [31].…”
Section: Introductionmentioning
confidence: 99%